EFEK SISA DAN TAMBAHAN TITONIA TERHADAP SIFAT KIMIA ULTISOL DAN HASIL TANAMAN jagung PADA MUSIM TANAM KE TIGA - Nurhajati Hakim; Irwan Darfis; Lia Arfania (Jurnal Solum, 2007)
Last researchers reported that Tithonia diversifolia (Mexican sunflower) could replace 25% to 50% of N and K of commercial fertilizer applied in  chili production on the first and second planting time in the Ultisols of West Sumatra.  A Continuation field experiments was conducted to find out the the appropriate NK cobination sources should be added on the third season to get the higest yield of maize. The treatments were the combination of NK T. diversifolia + NK commercial fertilizer which is maize needed. There were 9 treatmens such as A(0%+0%); B(0%+0%); C(50%+25%); D (50%+25%); E(25%+75%); F(25%+75%); G(50%%+50%); H(50%%+50%); and Control (0+100%). The results showed that integrated use 50% NK from tithonia with 25% NK from commercial fertilizer is the appropriate NK combination to get the higest yield (5ton ha-1)of  maize on the third season in Ultisols, if on the first season for chili planting time have reseived as 50% + 50% and on the second season for chili planting as much 25%+75% NK from titonia and NK from commercial fertilizerKey Words : Ultisols, tithonia, corn